Facility Rating Standards Review and Proposed Methodology for FERC Order 881 AAR Calculation - Bernardo Benigni; Olga Lavrova; Orland Whitney; Curt Feinberg (IEEE Access)
FERC rule 881 requires the use of ambient-adjusted ratings (AAR) instead of standard static line ratings (SLR) to ensure more precise assessments of the maximum transfer capability of transmission lines. AAR offers several advantages, resulting in improved transfer capacities. However, the practical details of calculations of AARs require careful and detailed consideration. This paper describes the rationale, procedures and technical references used as a basis for determining AARs for FERC Order 881 compliance. IEEE standards concerning the individual power facilities are reviewed for references to ambient temperature and solar heating. The formulas, references and other relevant information are consolidated in the paper providing the necessary information to perform AAR calculations. Additionally the paper provides recommendations on developing, where applicable, conservative equipment-type rating scaling factors to be used across a utility’s fleet.